Perbedaan Pengaruh Functional Strength Training dan Neuro Developmental Treatment pada Pasien Stroke dengan Gangguan Motorik Kasar Berdasarkan Parameter Gait Speed di RS. Rujukan Stroke Nasional Bukit Tinggi Tahun 2009 (Lembaga Penerbitan Universitas Esa Unggul, 2009)
Aim: to detect patient ability average result does movement motorik coarse (step speed usually and speed maximum) before and after done intervention functional strength training based on parameter gait speed and to detect patient ability average result does movement motorik coarse (step speed usually and speed maximum) before and after done intervention neuro-developmental treatment based on parameter gait speed, with to detect ability comparison influence in do movement motorik coarse (step speed usually and speed maximum) by using parameter gait speed in group at give intervention functional strength training and neuro-developmental treatment. at RS. Rujukan Stroke Nasional Bukit Tinggi in 2009. Method: this watchfulness has quation eksperimental to detects effectiveness influence before and after do intervention FST and NDT towards sufferer stroke with disturbance motorik coarse by using design pre - post. This watchfulness is done at hospital. Reference stroke tall hill national west Sumatra, time that need in this watchfulness is begun from June until July 2009. Population patient stroke with age between 50-70 year at take care of at RSUP tall hill commencing from June - July 2009 as much as 177 person. Sample population that fulfil standard criteria inclution and eksclution. Big sample appointeds with belief degree 90% and persisi (d) = 0,2 with total 17 person every intervention groups so that overall sample from intervention group FST and NDT, number 34 person. Result: happen average change in gait speed step usually (lb) before and after intervention FST as big as 6,59, indigoly p = 0,15(>0,1, in gait speed step maximum average change before and after intervention FST as big as 4,1, with value p = 0,36(>0,1) so from value p step usually and maximum demo not found difference that have a meaning between before and after in intervention 1. Value gait speed step usually after given intervention ndt got value p = 0,007 (< 0,1) and step maximum after given intervention ndt found value p = 0,016(<0,1) mean there difference that have a meaning for value gait speed before and after given intervention. Found difference that have a meaning value gait speed step usually and maximum step in intervention group 1 and 2 before and after do intervention.Keywords: Functional Strength Training, Neuro Developmental Treatment, Gait Speed